The Optimum Simulation Analysis of Sustainable Microgrid Electricity System Based on Hybrid Power Plant on Tunda Island, Banten Province - Paranai Suhasfan; Eko Adhi Setiawan (Publikasi Indonesia, 2022)
Tunda Island is one of the islands in a group of 17 islands in the north of Java, Banten Province. Electrical energy in Tunda Island is supplied by 2 Private Diesel Genset, each of which has an installed capacity of 100 kVA and 75 kVA, with an operating time of 4-5 hours per day starting from 18.00 to 22.00. The microgrid electrical system has several advantages, in terms of efficiency, microgrid can reduce the use of fossil fuels in power plants, besides that it can reduce losses caused by the distribution system because the location of the microgrid generator is relatively close to the load. In terms of reliability, the microgrid electrical system can optimally manage energy sources for 7 days and 24 hours. In addition, the microgrid electrical system has the ability to work without being connected to the grid. With the use of a microgrid electricity system, the electricity costs that must be paid are less and most importantly can reduce carbon emissions, because the plants used in the microgrid electricity system generally use renewable energy. In this study, scenarios were made to determine the most optimum LCoE value using an optimization approach with the help of homer pro software. The operating pattern for the Tunda Island electricity system is obtained, namely, the load is carried during the day by Solar PV Power Plant and at night using a generator that has been controlled using the force on & force off mode. From the simulation obtained the lowest LCoE in the Solar PV Power Plant Hybrid configuration with capacity of 240 KWp, 302.4 KWh battery & 200 KW inverter. The ability to pay for electricity for the residents of Tunda Island is still possible if subsidized tariffs are imposed, the range of ability to pay for the residents of Tunda Island is IDR/KWh 726.45-1452.91 and their ability will decrease if they are subject to non-subsidized PLN tariffs. With PLN as the PSO, the differrence in tariffs with the local Generation Production Cost will receive a subsidy from the government. Furthermore, the sustainability of this microgrid system will have the benefit of a continuous supply of electricity. So, it can be felt by the people of Tunda Island which is managed by State-Owned Enterprise (PT. PLN Persero).